Pengaruh pengetahuan keuangan dan sosialisasi keuangan keluarga terhadap perilaku pengelolaan keuangan dimoderasi toleransi risiko keuangan. - Nabilah, Nida Nur; Wardani, Dewi Kusuma; Sabandi, Muhammad (Jurnal Pendidikan Ekonomi (JUPE), 2024)
The topic is related to factors that can contribute to the financial management behavior and has not been extensively researched by previous researchers. This study aimed to examine the influence of financial knowledge and family financial socialization on the financial management behavior with financial risk tolerance as a moderating variable. This research approach employed is quantitative with a survey method. The sample consists of 269 active Diploma and Bachelor’s degree students at Universitas Sebelas Maret was taken using proportionate stratified random sampling. Data was collected through an online questionnaires with a Likert scale of 1-5. Data analysis was conducted using moderated regression analysis with SmartPLS software. The research results show that financial knowledge and family financial socialization influence financial management behavior. Additionally, financial risk tolerance has also been proven to moderate the relationship between financial knowledge and family financial socialization on financial management behavior. This research is useful for educational institutions, parents, and stakeholders interested in promoting the financial management behavior of students